Perlindungan Hukum Terhadap Korban Kekerasan Dalam Rumah Tangga Perspektif Hak Asasi Manusia - Apsari, Made Setyawati (Belom Bahadat, 2025)
Domestic violence (DV) is a very serious form of human rights violation, considering the physical, psychological, and social impacts it has on victims. Although various legal efforts have been made to provide protection for victims of domestic violence, there are still many obstacles in the implementation of effective legal protection. The purpose of this study is to analyze legal protection for victims of domestic violence from a Human Rights (HAM) perspective, by highlighting the extent to which the Indonesian legal system provides adequate protection in accordance with international human rights standards. The method used in this study is a normative approach with a literature review of laws, related regulations, and relevant literature. The results of the study indicate that although there are several regulations that provide legal protection, such as Law Number 23 of 2004 concerning the Elimination of Domestic Violence, the implementation of protection is still limited. Several factors that hinder effective protection include the lack of legal awareness in the community, obstacles in law enforcement, and minimal psychosocial support for victims. Therefore, further efforts are needed to increase legal awareness, strengthen law enforcement, and provide more comprehensive services for victims of domestic violence so that victims' human rights can be optimally protected.